PERPINDAHAN MASYARAKAT PLUTAN KE NAGARI MUARO KIAWAI KECAMATAN GUNUNG TULEH KABUPATEN PASAMAN TAHUN 1993-2012 - Reziati, Leni - (Pendidikan Sejarah, 2014)
This paper discusses the Peoples Movement Plutan to Nagari Muaro Kiawai Gunung Tuleh West Pasaman 1993-2012. The formulation of the problem in this study are as follows: How is the Public Switching Plutan in Nagari Muaro Kiawai Gunung Tuleh of years 1993-2012 and How Community Development Plutan displacement in Nagari Muaro Kiawai Gunung Tuleh from year 1993 to 2012. This study aims to describe the development of the Movement For The Nagari Community Plutan Muaro Kiawai Gunung Tuleh. Based on the purpose of the research methods used in this study is the method of historical research through four steps: (1) Heuristic is looking for data and collect data (information) from primary sources and secondary sources. Primary sources are obtained through oral sources with interviews with indigenous peoples and communities Plutan. (2) Criticism sources including external and internal criticism is to perform testing of the authenticity of the data (information). (3) Interpretation of interpreting data and connecting facts on the ground. (4) Historiography ie the presentation of research results in the form of a thesis. The results showed that at the beginning of the coming society in Nagari Muaro Plutan Kiawai very poor life, the socio-economic development in Nagari Muaro Plutan Kiawai when a change in the livelihood of the agricultural sector are turning kepekebunan palm. At the beginning of the coming society Plutan livelihood farming alone, but now it has increased revenues by oil palm plantations have started earning causing changes in socio-economic field. Based on the results of the study concluded that, with the transition livelihood from agriculture perkebuanan kesektor palm switch, then their lives become more developed and increased. With todays economy Plutan community has been able to build a house, buy a car as well as home furnishings and send their children kejenjang higher. Social interactions that occur among people Plutan with the natives are good it is proved by the presence of a mixture perkawianan made public if Plutan with the natives.